Solution:
A function with an input of 1 has an output of 3.
This means that
[tex]when\text{ }x=1,y=3[/tex]Step 1:
We will try the first option
[tex]\begin{gathered} y=3x \\ y=3(1) \\ y=3 \\ (1,3) \end{gathered}[/tex]Step 2:
We will try the second option
[tex]\begin{gathered} y=-x+4 \\ y=-1+4 \\ y=3 \\ (1,3) \end{gathered}[/tex]Step 3:
We will try the third option
[tex]\begin{gathered} y=x-2 \\ y=1-2 \\ y=-1 \\ (1,-1) \end{gathered}[/tex]Step 4:
We will try the fourth option
[tex]\begin{gathered} y=2x+1 \\ y=2(1)+1 \\ y=2+1 \\ y=3 \\ (1,3) \end{gathered}[/tex]Hence,
The final answer is
[tex]\Rightarrow y=x-2[/tex]